Improving History Learning Outcomes Through the Implementation of A Snowball Throwing Type Cooperative Learning Model in Class Xi at Binjai Methodist High School - Kaban, Benny Junior; Hardiyansyah, Muhammad Ricky; Darma, Aditya; Nugraha, Muhammad Adika (Education & Learning, 2024)
This research aims to improve student learning outcomes in history subjects by using a snowball-throwing cooperative model. This research is classroom action research (PTK), which was carried out in two cycles. The research was carried out at Binjai Methodist High School. The research period was carried out for five months, namely from June to July 2017. The research subjects were students of class XI-IPA-3 for the 2017-2018 academic year, totaling 23 people. The object of the research is history learning by applying snowball throwing-type learning. Data collection methods include observation and testing. The data collection instrument consists of data collection tools and data validity (validity of question items and level of difficulty of questions). Data analysis techniques include qualitative and quantitative data. The research procedure starts with the pre-cycle, cycle 1 and cycle 2. The target success indicators created by the researcher are pre-cycle 40%, cycle 1 (50%), and cycle 2 (75%). The results of the research showed that the increase was not too high in the first cycle; for this reason, the researchers made several changes in the second cycle. After improvements were made in the second cycle, there was an increase in student learning outcomes. From the research results, it was found that 39% of students completed the first cycle; after improvements were made in the second cycle, this increased to 78%. So learning history using the snowball throwing type can improve student learning outcomes. Based on this research, it can be concluded that the implementation of the snowball throwing cooperative model can improve student learning outcomes in history subjects in class XI Science 3 at Binjai Methodist High School.